Influence of Social Media Use on Sexual Behaviour of Undergraduate Students in Ilorin, Kwara State, Nigeria - Olayinka A Onasoga; Joel A Aluko; Nisola Sweet Adegbuyi; Adeniyi A Filade; Halima I. B. Shittu (Interdisciplinary Journal of Education, 2020)
Despite the fact that social media enhances learning opportunities and increases access to information, it has also paved way for exposure to illicit sexual content online and misuse of social sites which has been linked to risky sexual behaviour among undergraduates. Therefore, an institutional-based cross-sectional design was utilized to determine the influence of social media use on sexual behaviour of undergraduate students in Ilorin, Kwara State, Nigeria. Purposive sampling technique was used to select a sample size of 315 bonafide students. Data were collected using self-developed structured questionnaires and the same were analysed using descriptive and inferential statistics with level of significant set at 5% (0.05). The study revealed that all of the respondents 304 (100.0%) had access to internet and the majority 264 (86.8%) accessed the internet using mobile phones. Only 100(32.9%) of the respondents had high exposure to sexual content on social media and significant difference was observed in the extent of exposure to sexual contents via social media between the genders of participant with more males using social media for sexual purposes than females. The findings of the study also showed that there is significant association between exposure to sexual contents on social media and risky sexual behaviour among undergraduate students. Therefore, there is need for university authorities, parents and other stakeholders to plan interventional strategies to curb the use of social media to view illicit sexual content among undergraduate students.